Back Cover: Alkali Carbonate Molten Salt Coated Calcium Oxide with Highly Improved Carbon Dioxide Capture Capacity (Energy Technol. 8/2017). Issue 8 (29th May 2017) - Huang, Liang; Zhang, Yu; Gao, Wanlin; Harada, Takuya; Qin, Qingqing; Zheng, Qianwen; Hatton, T. Alan; Wang, Qiang
Abstract : CO2 capture worth its salt : Molten salt promotion offers a new measure to deal with diffusive limitation and enhance the CO2 capture capacity of commercial CaO. By loading alkali metal salts on the CaO surface, which transforms into liquid phase (white zone to the left of the circle) at a specific temperature, a high concentration of oxide ions (O 2‐ ) was provided to accelerate the transmission of carbonate (CO3 2‐ ) during the second stage. As the gas mixture makes its way through this material, CO2 reacts with O 2‐ to form free CO3 2−, which is easily transmitted, instead of forming unidentate carbonates that obstruct the generation of carbonate ions. As a result of this promotional effect, the uptake amount of CaO was increased and reaction temperature was reduced, with pure H2 able to be produced at the same time. More details can be found in the Full Paper by Liang Huang et al. from Beijing Forestry University (China) with collaborators from Massachusetts Institute of Technology onpage 1328 in Issue 8, 2017 (DOI:10.1002/ente.201600628 ).